Laparoscopic Intervention to Pancreatic Pseudocyst Confers Short-Term Benefits: A Meta-Analysis - Yulin Guo; Shun Hu; Shuo Wang; Ang Li; Feng Cao; Fei Li (Emergency Medicine International)
Background. Surgical interventions for pancreatic pseudocyst (PP) are traditionally managed by an open surgical approach. With the development of minimally invasive surgical techniques, a laparoscopic surgical approach for PPs has been conducted increasingly with comparable outcomes. The present study was conducted to compare the efficacy and safety of surgical intervention for PPs between the laparoscopic approach and the open approach. Methods. Databases including Cochrane Library, PubMed, and EMBASE were searched to identify studies that compared the safety and efficacy of surgical intervention for PPs between the laparoscopic approach and the open approach (until Aug 1st 2020). Results. A total of 6 studies were eligible in qualitative synthesis. The laparoscopic approach was associated with less intraoperative blood loss (MD = −69.97; 95% CI: −95.14 to −44.70, P<0.00001; P=0.86 for heterogeneity) and shorter operating time (MD = −33.12; 95% CI: −62.24 to −4.00, P=0.03; P<0.00001 for heterogeneity). There was no significant difference found between the two approaches regarding the success rate and the recurrence rate. The postoperative complications and mortality rates were comparable between the two approaches. Conclusions. The laparoscopic approach for the surgical intervention of PPs is safe and efficacious with shorter-term benefits.